PROMOTION OF UKRAINE’S CULTURAL DIPLOMACY IN THE EU - Pipchenko, Nataliya; Moskalenko, Taras (Politologija, 2017)
The paper provides an overview of existing research on Ukraine’s cultural diplomacy and sets the framework for further research. In other sections, the gathered practical insights about Ukraine’s cultural activity abroad and in the EU can be applied to the development of a new approach to the promotion of national interests and the examination of their impact on the current state of regional cooperation. The main time period covered in this study is the time after 2014, when Ukraine signed the Association Agreement with the EU. The paper uses a descriptive and interpretative approach, which is based on the review of previous research, as well as documentary and institutional analysis. It was found that the promotion of Ukrainian cultural products contributes to the deepening of the state’s integration into Europe and the developing of political, economic and civic relations between Ukraine and other countries of the region. The most important purpose of cultural activities approaching Ukraine to Europe is the prudent and consistent strategy of integrating the state in the European information space and the spread of positive information about Ukraine in European media. The research of the promotion of Ukraine’s cultural diplomacy in the EU made it possible to determine that the state’s perception by the European community is formed under the influence of several factors, in particular, national, tourist, social, political as well as economic. The paper draws conclusions about the main components of Ukraine’s cultural diplomacy strategy in the EU, which can be an area for further research. As a result of this, the main components of Ukraine’s cultural diplomacy strategy in the EU may be the explanation of Ukraine’s historic heritage, cultural and religious contacts with the European countries; communication with the international community about the great historic, cultural and religious heritage of Ukraine, unique travel opportunities and security; support of the famous European artists visits to Ukraine; the participation of Ukrainian artists in European art events; the attraction of the audience to using Ukrainian art products; the establishment of a joint Ukrainian-European forum on sensitive historic events to explain their historic background.